Estratégias de Redução de Custos em Nuvem sob a Perspectiva do Usuário: Um Mapeamento Sistemático - Soares, Elisa de Fátima Andrade; Cavalcanti, David Junio Mota; Sette, Ioram Schechtman; Ferraz, Carlos André Guimarães (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16088, 2025)
Cloud-based systems operate under a pay-per-use pricing model, which brings challenges related to budget cost management. Cloud financial management, anchored in FinOps principles, balances performance with budget control. Existing cloud cost management solutions have explored different approaches, such as resource requirement estimation, historical data analysis, and automated scaling decisions, which are already widely adopted. However, existing studies still lack a comprehensive view of cost optimization strategies, which vary between user and provider perspectives, and there is no way to classify or choose the most appropriate approach for every scenario. In this context, this paper proposes a systematic mapping study covering cloud cost reduction strategies from the user’s perspective. In particular, a complete methodology approach was defined by formulating detailed research questions, using carefully crafted search strings in scientific databases, and establishing organized by and structured by (processing, storage, network), strategy, type strategy, service type, cloud type and resource. Finally, emerging trends, research gaps, and practical implications for industry and academia are discussed.